Displacement e Interseções entre Espaço e Identidade em Voyage in the Dark, de Jean Rhys, e The Lonely Londoners, de Sam Selvon - Cruz, Mariana Batista da (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
Both Jean Rhys‟ Voyage in the Dark and Sam Selvon‟s The Lonely Londoners articulate the experiences of exile and otherness by subverting the traditional conventions of the English novel, encoding the fractured perception of space of the postcolonial subject through an engagement with typically modernist discursive forms. This paper examines how representations of displacement in these two narratives, as both a physical and psychological phenomenon, contribute to shape the postcolonial identity of their Caribbean exiles within British society. It will do so by considering the characters‟ relationship to and movement within London‟s social spaces, as well as their subjective experience of the material and imaginary spaces between which their double consciousness is divided. The goal is to reach a better understanding of how this rootlessness unsettles collective and individual postcolonial identities and how displacement may flourish into a subversive and aesthetically productive force.